Gender integration in livestock and fish research - Randolph, Thomas F. (International Livestock Research Institute, 2016)
Tom Randolph explains how gender research has evolved in the CGIAR Research Program on Livestock and Fish: when engaging in inclusive value chain development and improving access to food for the poor, addressing gender is inevitable. Livestock keepers and value-chain actors are often women; research has shown that they benefit from their activities, but often not by as much as they should. The food they produce is meant to improve nutrition, a field in which women are key. In navigating between strategic research and mainstreaming gender while exploring accommodative and transformative approaches, the Livestock and Fish Program has collected important evidence on the kind of research needed for development and has laid the basis for the next series of CGIAR research programs. Interview with Thomas F. Randolph (CGIAR Research Program on Livestock and Fish) for the book "A different kettle of fish? Gender integration in livestock and fish research". http://hdl.handle.net/10568/76684